Flower-like NiO for the detection of 3-methyl-1-butanol, a microbial volatile organic compound - Vioto, Gabriel C.N. [UNESP]; Perfecto, Tarcísio M. [UNESP]; Zito, Cecilia A. [UNESP]; Volanti, Diogo P. [UNESP] (Elsevier, 2023)
Volatile organic compounds (VOCs) can indicate the quality or freshness of food. Thus, the development of VOC sensors has a tremendous technological impact. Herein, we report the VOC sensing performance of porous flower-like NiO to 3-methyl-1-butanol (3M1B), a microbial VOC that can be used as a food spoilage marker. Our results show that the NiO-based sensor has high sensitivity and selectivity to 3M1B compared to the other VOCs, including acetone, ethanol, butanone, 2-nonanone, and m-xylene. Moreover, we show that NiO exhibits a high response to 3M1B with fast response times under humidity conditions, being a promising material for real applications.
Keywords: Chemoresistive; Gas sensor; Microbial volatile organic compounds; α-Nickel hydroxide